INTERWEAVING CONCEPTUAL AND SUBSTANTIAL PROBLEMS OF WRITING INSTRUCTION: SOCIO REFLECTIVE ON EXPLORING HORTATORY AND ANALYTICAL EXPOSITION - Afifah, Wiwiek; Sarudin, Anida (Universitas Ahmad Dahlan, 2020)
This paper explores interweaving conceptual and substantial problems of teaching writing skills for analytical and hortatory exposition texts. Under the narrative inquiry, five English teachers? personal life experiences were analyzed. Having been analyzed, the findings reveal: (1) students were still weak in understanding the concept of the two texts (social function, generic structure, and lexicogrammatical features of the text). (2) Students? confusion to distinguish the two genres is supported by the condition that they do not learn the genres in their primary language. (3) The students are not accustomed to expressing their arguments whereas in analytical and hortatory texts the main points are presenting sequences of arguments in the body of the text. (4) Students have low motivation to read therefore it is hard for them to propose the suggestion and make reiteration in the end of hortatory and analytical exposition texts, and (5) lexicogrammatical features or the grammar that are commonly used in those texts are complex for the students in that level.